Responses of native plants of the Patagonian steppe to reduced solar radiation caused by exotic coniferous plantations: a nursery approach - Rago, María Melisa (2022)
In exotic coniferous plantations established in treeless environments, light availability is drastically reduced, limiting the development of the native herb–shrub layer and consequently ecosystem functions and services. However, plants exhibit different responses to deal with changes in the light environment. Aiming to contribute to management guidelines favoring understory vegetation persistence in forest plantations, we evaluated, under nursery trial, the growth of three representative species of the Patagonian steppe at 20, 60, and 100% irradiance. For each species, we compared, among treatments, total biomass, biomass allocation, and specific leaf area several times during two growing seasons, relative growth rate, net assimilation rate, and leaf area ratio at each time interval, and reproductive structures the second growing season. Berberis microphylla and Adesmia volckmannii maintained their total biomass at 60% irradiance, with A. volckmannii showing a tendency to increase it, whereas Poa ligularis tended to decrease total biomass at irradiances below 60%. For the three species, changes in biomass allocation, generally higher leaf mass fraction, and higher specific leaf area were detected at 20% and sometimes at 60% irradiance. Relative growth rate and net assimilation rate, in general, tended to be higher at 60 and 100% irradiance, whereas leaf area ratio was higher at 20% and sometimes at 60% irradiance. Adesmia volckmannii and P. ligularis had fewer reproductive structures at 20% irradiance. These results suggest that the analyzed species present a certain level of shade tolerance, at least up to 60% irradiance, that may benefit their development in forest plantations with appropriate management.